Seasonal performance and behaviour of Nellore cattle in integrated crop-livestock systems - Aranha, A. S. [UNESP]; Andrighetto, C. [UNESP]; Mateus, G. P.; Santana, E. A.R. [UNESP]; Lupatini, G. C. [UNESP]; Aranha, A. R.; Fonseca, R. [UNESP]; Sekiya, B. M.S. [UNESP]; Bueno, L. G.F. [UNESP]; Meirelles, P. R.L. [UNESP]; Maestá, S. A. [UNESP]; da Luz, P. A. [UNESP]; et al. (My University, 2022)
The first objective of this study was to assess Marandu palisade grass in an integrated crop-livestock system (ICL), and two integrated crop-livestock-forest (ICLF) systems. The first ICLF had a single row of eucalyptus (ICLF-1L) and the second had three rows of eucalyptus (ICLF-3L). The second objective was to assess the performance, behaviour, and thermal comfort of Nellore cattle in these systems during summer and winter. The data were collected for two years after the systems were implemented. Sixty Nellore cattle were used. Dry forage mass (DFM) was similar in all systems with a higher percentage of leaves observed in ICLF-3L in winter compared with ICL. Forage in the ICLF-1L and ICLF-3L systems contained more crude protein (CP) than ICL. The radiant thermal load was lower for ICLF-1L and ICLF-3L, with a lower globe temperature in ICLF-3L. The stocking rate was lowest for ICLF-3L. Two years after the systems had been established, the trees provided low density shade and implementing the ICLF-1L and ICLF-3L systems improved the CP content of the grass without changing the levels of DFM and performance of the cattle. The trees reduced the total thermal energy exchanged between the animal and the environment, improving thermal comfort, but did not influence cattle behaviour or their haematological parameters.
Keywords: agrosilvopastoral; forage quality; productivity; thermal comfort